Pre-hospital Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA) for exsanguinating pelvic haemorrhage. (February 2019) - Lendrum, Robbie; Perkins, Zane; Chana, Manik; Marsden, Max; Davenport, Ross; Grier, Gareth; Sadek, Samy; Davies, Gareth
Abstract: Aim: To report the initial experience and outcomes of Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA) as an adjunct to pre-hospital resuscitation of patients with exsanguinating pelvic haemorrhage. Methods: Descriptive case series of consecutive adult patients, treated with pre-hospital Zone III REBOA by a physician-led pre-hospital trauma service, between January 2014 and July 2018. Results: REBOA was attempted in 19 trauma patients (13 successful, six failed attempts) and two non-trauma patients (both successful) with exsanguinating pelvic haemorrhage. Trauma patients were severely injured (median ISS 34, IQR: 27–43) and profoundly hypotensive (median systolic blood pressure [SBP] 57, IQR: 40–68 mmHg). REBOA significantly improved blood pressure (Pre-REBOA median SBP 57, IQR: 35–67 mmHg versus Post- REBOA SBP 114, IQR: 86–132 mmHg; Median of differences 66, 95% CI: 25–74 mmHg; P < 0.001). REBOA was associated with significantly lower risk of pre-hospital cardiac arrest (REBOA 0/13 [0%] versus no REBOA 3/6 [50%], P = 0.021) and death from exsanguination (REBOA 0/13 [0%] versus no REBOA 4/6 [67%], P = 0.004), when compared to patients with a failed attempt. Successful REBOA was associated with improved survival (REBOA 8/13 [62%] versus no REBOA 2/6 [33%]; P = 0.350). Distal arterial thrombus requiring thrombectomy was common in the REBOA group (10/13, 77%). Conclusion: REBOA is a feasible pre-hospital resuscitation strategy for patients with exsanguinating pelvic haemorrhage. REBOA significantly improves blood pressure and may reduce the risk of pre-hospital hypovolaemic cardiac arrest and early death due to exsanguination. Distal arterial thrombus formation is common, and should be actively managed.